2019
DOI: 10.1002/chem.201901803
|View full text |Cite
|
Sign up to set email alerts
|

PtII‐Catalyzed Hydroxylation of Terminal Aliphatic C(sp3)−H Bonds with Molecular Oxygen

Abstract: The practical application of Shilov‐type Pt catalysis to the selective hydroxylation of terminal aliphatic C−H bonds remains a formidable challenge, due to difficulties in replacing PtIV with a more economically viable oxidant, particularly O2. We report the potential of employing FeCl2 as a suitable redox mediator to overcome the kinetic hurdles related to the direct use of O2 in the Pt reoxidation. For the selective conversion of butyric acid to γ‐hydroxybutyric acid (GHB), a significantly enhanced catalyst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The authors demonstrated that both reactivity and selectivity could be improved either by the addition of 2-pyridone as a ligand or by the addition of boric acid to stop the oxidation process at the stage of GHB. 14 Lee and Chang used a related catalytic system in 2006 to achieve the lactonization of ortho-methyl-substituted benzoic acid derivatives (Scheme 3, a). 15 For example, using 2,4,6-trimethylbenzoic acid (8a) as the substrate the authors isolated the corresponding lactone 9a in 56% yield.…”
Section: The Lactonization Of Aliphatic Carboxylic Acidsmentioning
confidence: 99%
“…The authors demonstrated that both reactivity and selectivity could be improved either by the addition of 2-pyridone as a ligand or by the addition of boric acid to stop the oxidation process at the stage of GHB. 14 Lee and Chang used a related catalytic system in 2006 to achieve the lactonization of ortho-methyl-substituted benzoic acid derivatives (Scheme 3, a). 15 For example, using 2,4,6-trimethylbenzoic acid (8a) as the substrate the authors isolated the corresponding lactone 9a in 56% yield.…”
Section: The Lactonization Of Aliphatic Carboxylic Acidsmentioning
confidence: 99%
“…To be mentioned, van Gemmeren's short review on direct C(sp 3 )−H activation of carboxylic acids provided a brief overview of different C−H functionalizations [14] . Few examples for C(sp 3 )−H lactonization [15] and hydroxylation [16] of carboxylic acids were reported under platinum catalysis. They are not included in this report.…”
Section: Introductionmentioning
confidence: 99%
“…alkyl ammonium salts, as well as lower carboxylic, sulfonic and phosphonic acids. 21,22 Hence, Shilovinspired Pt catalysis has hitherto not been applied for the selective oxidation of non-polar aliphatic compounds. While we demonstrated the potential of implementing acetic acid as a solvent in converting n-heptane to 1-heptanol, 23 the use of an aqueous solution would be highly desirable from an ecological perspective.…”
Section: Introductionmentioning
confidence: 99%